Preparation method of sound insulation and noise reduction sponge and application of sound insulation and noise reduction sponge in air conditioner

By adding cellulose nanocrystals and polyepoxy quaternary ammonium salt crosslinking agent to the polyvinyl alcohol sponge, combined with foaming and curing treatment, the problems of poor mechanical strength, antibacterial properties and sound absorption and noise reduction performance of the polyvinyl alcohol sponge are solved, and higher tensile strength and sound absorption performance are achieved, and antibacterial and mildew resistance are significantly improved.

CN119798761AActive Publication Date: 2025-04-11ZHUHAI ZHONGYA AIR CONDITIONING ACCESSORIES CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510070015.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-11
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

The mechanical strength, antibacterial properties and sound absorption and noise reduction properties of polyvinyl alcohol sponges are poor.

Method used

By adding potassium hydroxide to water to adjust the pH, adding cellulose nanocrystals and polyepoxy quaternary ammonium salt crosslinking agent, adding surfactant and sodium bicarbonate after stirring and foaming and curing, a quaternary ammonium modified cellulose-polyvinyl alcohol sponge was prepared.

Benefits of technology

The tensile strength and mechanical properties of the sponge material are improved, and the sound absorption coefficient reaches 0.675-0.813, which significantly improves the antibacterial and mildew resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005245900690000021
    Figure BDA0005245900690000021
  • Figure BDA0005245900690000022
    Figure BDA0005245900690000022
  • Figure BDA0005245900690000071
    Figure BDA0005245900690000071
Patent Text Reader

Abstract

The invention relates to the technical field of polyvinyl alcohol sponges, and discloses a preparation method of a sound insulation and noise reduction sponge and application of the sound insulation and noise reduction sponge in an air conditioner, and the sound insulation and noise reduction sponge is obtained by mixing a surfactant, quaternary ammonium salt modified cellulose-polyvinyl alcohol, sodium bicarbonate, a formaldehyde aqueous solution and a sulfuric acid solution, stirring for foaming and heating for curing forming. The polyvinyl alcohol is used as a sponge base body, the grafted cellulose nanocrystalline is used as a reinforcing agent, and the sponge material obtained through foaming has higher tensile strength and sound absorption coefficient, good mechanical property and strong sound absorption, sound insulation and noise reduction performance. The polyepoxy quaternary ammonium salt cross-linking agent contains a large number of quaternary ammonium salt groups and is chemically cross-linked into a polyvinyl alcohol sponge matrix, so that the antibacterial and mildew-proof properties of the sponge material are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyvinyl alcohol sponge, in particular to a preparation method of a sound insulation and noise reduction sponge and application of the sponge in an air conditioner. Background Art

[0002] Foam sponge materials for air conditioners mainly play the role of filtering dust, absorbing bacteria, reducing noise, etc., and play the role of reducing dust pollution, sterilizing and preventing mildew, sound insulation and noise reduction. Its sponge materials are mainly polyurethane foam sponge, polyethylene foam sponge, self-adhesive sponge, etc. Polyvinyl alcohol has the advantages of being cheap, easy to obtain, and biodegradable, and can be foamed to obtain foam sponge materials with excellent performance, which are widely used in the fields of sound insulation and heat preservation materials, drug sustained release, etc. Patent CN101508747B discloses melamine-modified polyvinyl alcohol formal foam material and its preparation method and application. The polyvinyl alcohol formal foam material prepared by using polyvinyl alcohol, melamine, formaldehyde, foaming agent, pore-forming agent, etc. as raw materials has the advantages of high mechanical strength and good temperature resistance, and can be used as medical sponge, sound insulation protection material, etc. However, the foam material does not show good sound insulation and noise reduction and antibacterial and mildew resistance. Summary of the invention

[0003] The invention solves the problem that the mechanical strength, antibacterial performance and sound absorption, sound insulation and noise reduction performance of the polyvinyl alcohol sponge are poor.

[0004] Technical solution: A method for preparing a sound insulation and noise reduction sponge:

[0005] Step A, adding potassium hydroxide to water to adjust the pH to 10-11, adding cellulose nanocrystals, stirring, adding polyvinyl alcohol aqueous solution and polyepoxy quaternary ammonium salt crosslinking agent, stirring and reacting at 45-60° C. for 6-12 hours, filtering, washing with water and ethanol, and drying to obtain quaternary ammonium salt modified cellulose-polyvinyl alcohol.

[0006] Step B, adding surfactant and quaternary ammonium salt-modified cellulose-polyvinyl alcohol to water, adding sodium bicarbonate, formaldehyde aqueous solution and sulfuric acid solution after heating and stirring, stirring and foaming for 10-20 minutes, and then heating and curing at 45-65° C. for 2-4 hours, washing with water, and drying to obtain a sound insulation and noise reduction sponge.

[0007] Preferably, in step A, the mass ratio of cellulose nanocrystals, polyvinyl alcohol, and polyepoxide quaternary ammonium salt crosslinking agent is (5-40):100:(1-6).

[0008] Preferably, the surfactant in step B is OP-10 or Triton X-100.

[0009] Preferably, the preparation method of the polyepoxide quaternary ammonium salt cross-linking agent is:

[0010] (1) Add toluene, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3-dimethylamino-1-propanol, and 4-dimethylaminopyridine to a reaction vessel, heat to 60-85°C, react for 3-5 hours, then cool to 20-30°C, add N,N-dicyclohexylcarbodiimide, continue to react for 12-18 hours, distill under reduced pressure, wash with water, and recrystallize the product in ethanol to obtain a tertiary amine precursor. The reaction formula is:

[0011]

[0012] (2) Add ethanol, tertiary amine precursor, epichlorohydrin and potassium sulfate to a reaction vessel, heat to 50-80°C, stir and react for 3-6 seconds, perform vacuum distillation, wash with water, and recrystallize the product in a mixed solution of ethanol and ethyl acetate to obtain a polyepoxy quaternary ammonium salt crosslinking agent. The reaction formula is:

[0013]

[0014] Preferably, the molar ratio of 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3-dimethylamino-1-propanol, 4-dimethylaminopyridine and N,N-dicyclohexylcarbodiimide is 1:(4.4-5.2):(0.4-0.48):(4.4-5.6).

[0015] Preferably, the molar ratio of the tertiary amine precursor, epichlorohydrin and potassium sulfate in (2) is 1:(4.4-4.8):(0.1-0.12).

[0016] Technical effect: The polyepoxy quaternary ammonium salt crosslinking agent of the present invention contains multiple epoxy groups, which can react with polyvinyl alcohol and hydroxyl groups of cellulose nanocrystals to form a ring-opening crosslinking reaction, thereby improving the interfacial bonding between the two and forming a tight and stable crosslinking network. At the same time, the molecular chain crosslinking network contains a rigid and stable biphenyl structure. With polyvinyl alcohol as the sponge matrix and grafted cellulose nanocrystals as the reinforcing agent, the sponge material obtained by foaming has higher tensile strength and mechanical properties. The sound absorption coefficient reaches 0.675-0.813, which has good sound absorption, sound insulation and noise reduction performance.

[0017] The polyepoxy quaternary ammonium salt crosslinking agent of the invention contains a large number of quaternary ammonium salt groups, which are chemically crosslinked into the polyvinyl alcohol sponge matrix, have strong inhibitory and killing effects on Staphylococcus aureus and Escherichia coli, and significantly improve the antibacterial and mildew-proof properties of the sponge material. DETAILED DESCRIPTION

[0018] The technical solution of the present invention is further described in detail below through specific implementation methods.

[0019] The polyvinyl alcohol in the specific implementation manner was obtained from Henan Youchuang Chemical Products Co., Ltd. Cellulose nanocrystals were obtained from Jiangsu Jufeng Chemical Technology Co., Ltd.

[0020] Example 1

[0021] (1) Add 20 mL of toluene, 5 mmol of 3,3',4,4'-biphenyltetracarboxylic dianhydride, 22 mmol of 3-dimethylamino-1-propanol, and 2.4 mol of 4-dimethylaminopyridine to a reaction vessel, heat to 60°C, react for 5 hours, then cool to 20°C, add 22 mmol of N,N-dicyclohexylcarbodiimide, continue to react for 18 hours, distill under reduced pressure, wash with water, and recrystallize the product in ethanol to obtain a tertiary amine precursor.

[0022] (2) Add 4 mL of ethanol, 3 mmol of tertiary amine precursor, 13.2 mmol of epichlorohydrin, 0.36 mmol of potassium sulfate, and 2 mL of water to a reaction container, heat to 50° C., stir to react for 3 h, distill under reduced pressure, wash with water, and recrystallize the product in a mixed solution of ethanol and ethyl acetate to obtain a polyepoxy quaternary ammonium salt crosslinking agent.

[0023] (3) Potassium hydroxide was added to 10 mL of water to adjust the pH to 10, and 0.5 g of cellulose nanocrystals was added. After stirring, 100 mL of an aqueous solution containing 10 g of polyvinyl alcohol and 0.1 g of a polyepoxy quaternary ammonium salt crosslinking agent were added. The mixture was stirred at 60° C. for 6 h, filtered, washed with water and ethanol, and dried to obtain quaternary ammonium salt-modified cellulose-polyvinyl alcohol.

[0024] (4) Add 0.6 g of surfactant OP-10 and 10 g of quaternary ammonium salt-modified cellulose-polyvinyl alcohol to 200 mL of water, heat and stir, add 2 g of sodium bicarbonate, 18 mL of formaldehyde aqueous solution (mass fraction 37%), and 36 mL of sulfuric acid solution (mass fraction 50%), stir and foam for 10 min, then heat and cure at 45 ° C for 4 h, wash with water, and dry to obtain a sound insulation and noise reduction sponge.

[0025] Example 2

[0026] (1) Add 25 mL of toluene, 5 mmol of 3,3',4,4'-biphenyltetracarboxylic dianhydride, 26 mmol of 3-dimethylamino-1-propanol, and 2 mol of 4-dimethylaminopyridine to a reaction vessel, heat to 85°C, react for 3 hours, then cool to 30°C, add 28 mmol of N,N-dicyclohexylcarbodiimide, continue to react for 12 hours, distill under reduced pressure, wash with water, and recrystallize the product in ethanol to obtain a tertiary amine precursor.

[0027] (2) 4 mL of ethanol, 3 mmol of tertiary amine precursor, 14.4 mmol of epichlorohydrin, 0.3 mmol of potassium sulfate, and 2 mL of water were added to a reaction container, heated to 80° C., stirred for reaction for 6 h, distilled under reduced pressure, washed with water, and the product was recrystallized in a mixed solution of ethanol and ethyl acetate to obtain a polyepoxy quaternary ammonium salt crosslinking agent.

[0028] (3) Add potassium hydroxide to 20 mL of water to adjust the pH to 10, add 1.5 g of cellulose nanocrystals, stir, add 100 mL of an aqueous solution containing 10 g of polyvinyl alcohol and 0.25 g of a polyepoxy quaternary ammonium salt crosslinking agent, stir and react at 45 ° C for 12 h, filter, wash with water and ethanol, and dry to obtain quaternary ammonium salt-modified cellulose-polyvinyl alcohol.

[0029] (4) Add 2 g of surfactant Triton X-100 and 10 g of quaternary ammonium salt-modified cellulose-polyvinyl alcohol to 200 mL of water, heat and stir, add 2 g of sodium bicarbonate, 15 mL of formaldehyde aqueous solution (mass fraction 37%), and 32 mL of sulfuric acid solution (mass fraction 50%), stir and foam for 20 min, then heat and cure at 65 ° C for 2 h, wash with water, and dry to obtain a sound insulation and noise reduction sponge.

[0030] Example 3

[0031] (1) Potassium hydroxide was added to 40 mL of water to adjust the pH to 10, and 2.8 g of cellulose nanocrystals were added. After stirring, 100 mL of an aqueous solution containing 10 g of polyvinyl alcohol and 0.4 g of a polyepoxy quaternary ammonium salt crosslinking agent (prepared according to the method of Example 1) were added. The mixture was stirred at 50° C. for 8 h, filtered, washed with water and ethanol, and dried to obtain quaternary ammonium salt-modified cellulose-polyvinyl alcohol.

[0032] (2) Add 0.6 g of surfactant OP-10 and 10 g of quaternary ammonium salt-modified cellulose-polyvinyl alcohol to 200 mL of water, heat and stir, add 6 g of sodium bicarbonate, 22 mL of formaldehyde aqueous solution (mass fraction 37%), and 36 mL of sulfuric acid solution (mass fraction 50%), stir and foam for 20 minutes, then heat and cure at 45°C for 3 hours, wash with water, and dry to obtain a sound insulation and noise reduction sponge.

[0033] Example 4

[0034] (1) Potassium hydroxide was added to 40 mL of water to adjust the pH to 11, 4 g of cellulose nanocrystals were added, and after stirring, 100 mL of an aqueous solution containing 10 g of polyvinyl alcohol and 0.6 g of a polyepoxy quaternary ammonium salt crosslinking agent (prepared according to the method of Example 1) were added, and the mixture was stirred at 45° C. for 12 h, filtered, washed with water and ethanol, and dried to obtain quaternary ammonium salt-modified cellulose-polyvinyl alcohol.

[0035] (2) Add 0.8 g of surfactant OP-10 and 10 g of quaternary ammonium salt-modified cellulose-polyvinyl alcohol to 200 mL of water, heat and stir, add 4 g of sodium bicarbonate, 16 mL of formaldehyde aqueous solution (mass fraction 37%), and 30 mL of sulfuric acid solution (mass fraction 50%), stir and foam for 10 min, then heat and cure at 60 ° C for 4 h, wash with water, and dry to obtain a sound insulation and noise reduction sponge.

[0036] Comparative Example 1

[0037] (1) Add 0.6 g of surfactant OP-10 and 10 g of polyvinyl alcohol to 200 mL of water, heat and stir, add 2 g of sodium bicarbonate, 18 mL of formaldehyde aqueous solution (mass fraction 37%), and 36 mL of sulfuric acid solution (mass fraction 50%), stir and foam for 10 min, then heat and cure at 45 ° C for 4 h, wash with water, and dry to obtain a sound insulation and noise reduction sponge.

[0038] Comparative Example 2

[0039] (1) 0.5 g of cellulose nanocrystals and 10 g of polyvinyl alcohol were stirred and mixed to obtain a cellulose-polyvinyl alcohol blend.

[0040] (2) Add 0.6 g of surfactant OP-10 and 10 g of cellulose-polyvinyl alcohol blend to 200 mL of water, heat and stir, add 2 g of sodium bicarbonate, 18 mL of formaldehyde aqueous solution (mass fraction 37%), and 36 mL of sulfuric acid solution (mass fraction 50%), stir and foam for 10 min, then heat and cure at 45 ° C for 4 h, wash with water, and dry to obtain a sound insulation and noise reduction sponge.

[0041] Comparative Example 3

[0042] (1) Potassium hydroxide was added to 10 mL of water to adjust the pH to 10, and 100 mL of an aqueous solution containing 10 g of polyvinyl alcohol and 0.1 g of a polyepoxy quaternary ammonium salt crosslinking agent (prepared according to the method of Example 1) were added, and the mixture was stirred at 60° C. for 6 h, filtered, washed with water and ethanol, and dried to obtain quaternary ammonium salt-modified polyvinyl alcohol.

[0043] (2) Add 0.6 g of surfactant OP-10 and 10 g of quaternary ammonium salt-modified polyvinyl alcohol to 200 mL of water, add 2 g of sodium bicarbonate, 18 mL of formaldehyde aqueous solution (mass fraction 37%), and 36 mL of sulfuric acid solution (mass fraction 50%) after heating and stirring, stir and foam for 10 min, then heat and cure at 45 ° C for 4 h, wash with water, and dry to obtain a sound insulation and noise reduction sponge.

[0044] Comparative Example 4

[0045] (1) Add 3 mL of ethanol, 3 mmol of N,N,N',N'-tetramethylethylenediamine, 6.6 mmol of epichlorohydrin, 0.18 mmol of potassium sulfate, and 1.5 mL of water to a reaction vessel, heat to 50°C, stir and react for 3 hours, distill under reduced pressure, wash with water, and recrystallize the product in a mixed solution of ethanol and ethyl acetate to obtain an epoxy quaternary ammonium salt crosslinking agent. The structural formula is

[0046] (2) Add potassium hydroxide to 10 mL of water to adjust the pH to 10, add 0.5 g of cellulose nanocrystals, stir, add 100 mL of an aqueous solution containing 10 g of polyvinyl alcohol and 0.1 g of a polyepoxy quaternary ammonium salt crosslinking agent, stir and react at 60° C. for 6 h, filter, wash with water and ethanol, and dry to obtain quaternary ammonium salt-modified cellulose-polyvinyl alcohol.

[0047] (3) Add 0.6 g of surfactant OP-10 and 10 g of quaternary ammonium salt-modified cellulose-polyvinyl alcohol to 200 mL of water, heat and stir, add 2 g of sodium bicarbonate, 18 mL of formaldehyde aqueous solution (mass fraction 37%), and 36 mL of sulfuric acid solution (mass fraction 50%), stir and foam for 10 min, then heat and cure at 45 ° C for 4 h, wash with water, and dry to obtain a sound insulation and noise reduction sponge.

[0048] The sponge was made into samples according to GB / T 6344-2008 standard, and the tensile strength of the sponge was tested using a universal material testing machine. The sound absorption coefficient of the sponge was tested according to GB / T 18696.1-2004 standard.

[0049] The antibacterial properties of the sponge were tested using the oscillating bottle method. 5 mL of a 10 6 cfu / mL of Staphylococcus aureus or Escherichia coli suspension was added to a test tube, 0.1 g of sponge was added (the sponge in Comparative Example 1 was a blank control sample), oscillated at 25 ° C for 3 h, the oscillation frequency was 200 r / min, and then phosphate buffer solution was added dropwise for 10-fold gradient dilution, 0.2 mL of the diluted bacterial solution was coated on an agar plate, and cultured at 37 ° C for 24 h in a constant temperature and humidity incubator. After culture, the colonies were counted and the inhibition rate was calculated.

[0050] Inhibition rate = (the number of colonies in the blank control sample - the number of colonies in the experimental sample) ÷ the number of colonies in the blank control sample × 100%.

[0051] Table 1 Sponge performance test

[0052]

[0053] After testing, the sound absorption coefficient of the sound insulation and noise reduction sponge prepared by Examples 1-4 reaches 0.675-0.813, and the tensile strength reaches 57.1-78.2MPa, with good sound absorption, sound insulation and noise reduction performance and tensile strength, and shows a high antibacterial rate to Staphylococcus aureus and Escherichia coli, and has excellent antibacterial performance. Mainly because the polyepoxy quaternary ammonium salt cross-linking agent contains multiple epoxy groups, can react with polyvinyl alcohol and the hydroxyl groups of cellulose nano-crystals to form an open-loop cross-linking reaction, improve the interfacial bonding force between the two, form a stable cross-linked network, and contain a rigid and stable biphenyl structure in the molecular chain cross-linked network, with polyvinyl alcohol as the sponge matrix, and the grafted cellulose nano-crystals as a reinforcing agent, the sponge material obtained by foaming has higher tensile strength and mechanical properties. And the polyepoxy quaternary ammonium salt cross-linking agent contains a large amount of quaternary ammonium salt groups, has a strong inhibitory and killing effect on Staphylococcus aureus and Escherichia coli, and significantly improves the antibacterial performance of the sponge material.

[0054] In Comparative Example 1, cellulose nanocrystals and polyepoxy quaternary ammonium salt crosslinking agent were not added, and the mechanical strength of the sponge material was low, and the antibacterial property was poor.

[0055] In Comparative Example 2, polyvinyl alcohol and cellulose nanocrystals are blended and foamed. The interfacial bonding force between the two is low, the compatibility is poor, a stable cross-linked network is not formed, and there is no rigid and stable biphenyl structure, resulting in low tensile strength of the sponge and poor antibacterial properties.

[0056] In Comparative Example 3, no cellulose nanocrystals were added, and the tensile strength of the sponge material was lower than that of Example 1.

[0057] The epoxy quaternary ammonium salt crosslinking agent in Comparative Example 4 has fewer epoxy groups and insufficient crosslinking sites, which prevents the polyvinyl alcohol and cellulose nanocrystals from forming a stable crosslinking network. At the same time, the molecular chain crosslinking network does not contain a rigid and stable biphenyl structure, resulting in the tensile strength of the sponge material being lower than that in Example 1.

[0058] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that the specific implementation methods of the present invention can still be modified or some technical features can be replaced by equivalents without departing from the spirit of the technical solution of the present invention, which should be included in the scope of the technical solution for protection of the present invention.

Claims

1. A method for preparing a sound insulation and noise reduction sponge, characterized in that: The preparation method comprises the following steps: Step A, adding potassium hydroxide and cellulose nanocrystals into water, stirring, adding an aqueous solution of polyvinyl alcohol and a polyepoxy quaternary ammonium salt cross-linking agent, stirring for reaction, filtering, washing, and drying to obtain quaternary ammonium salt modified cellulose-polyvinyl alcohol; The structural formula of the polyepoxide quaternary ammonium salt cross-linking agent is as follows: Step B, adding a surfactant and quaternary ammonium salt-modified cellulose-polyvinyl alcohol to water, adding sodium bicarbonate, formaldehyde aqueous solution and sulfuric acid solution after heating and stirring, stirring and foaming, heating and curing to form, washing and drying to obtain a sound insulation and noise reduction sponge.

2. The method for preparing the sound insulation and noise reduction sponge according to claim 1, characterized in that: In step A, potassium hydroxide is added to adjust the pH of water to 10-11.

3. The method for preparing the sound insulation and noise reduction sponge according to claim 1, characterized in that: The reaction temperature in step A is 45-60° C. and the reaction time is 6-12 h.

4. The method for preparing the sound insulation and noise reduction sponge according to claim 1, characterized in that: In the step A, the mass ratio of cellulose nanocrystals, polyvinyl alcohol, and polyepoxide quaternary ammonium salt crosslinking agent is (5-40):100:(1-6).

5. The method for preparing the sound insulation and noise reduction sponge according to claim 4, characterized in that: The preparation method of the polyepoxide quaternary ammonium salt cross-linking agent is: (1) Add toluene, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3-dimethylamino-1-propanol, and 4-dimethylaminopyridine to a reaction vessel, heat to 60-85° C., react for 3-5 hours, then cool to 20-30° C., add N,N-dicyclohexylcarbodiimide, continue to react for 12-18 hours, distill under reduced pressure, wash, and recrystallize to obtain a tertiary amine precursor; (2) Add ethanol, tertiary amine precursor, epichlorohydrin, potassium sulfate and water to a reaction vessel, heat to 50-80° C., stir to react for 3-6 seconds, perform vacuum distillation, wash and recrystallize to obtain a polyepoxy quaternary ammonium salt crosslinking agent.

6. The method for preparing the sound insulation and noise reduction sponge according to claim 5, characterized in that: The molar ratio of 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3-dimethylamino-1-propanol, 4-dimethylaminopyridine and N,N-dicyclohexylcarbodiimide in (1) is 1:(4.4-5.2):(0.4-0.48):(4.4-5.6).

7. The method for preparing the sound insulation and noise reduction sponge according to claim 5, characterized in that: The molar ratio of the tertiary amine precursor, epichlorohydrin and potassium sulfate in (2) is 1:(4.4-4.8):(0.1-0.12).

8. The method for preparing the sound insulation and noise reduction sponge according to claim 1, characterized in that: The stirring and foaming time in step B is 10-20 minutes, and the heating and curing temperature is 45-65° C. and the time is 2-4 hours.

9. The method for preparing the sound insulation and noise reduction sponge according to claim 1, characterized in that: The surfactant in step B is OP-10 or Triton X-100.

10. Use of the sound insulation and noise reduction sponge obtained by the preparation method according to any one of claims 1 to 9 in air conditioning.

Citation Information

Patent Citations

  • Microwave-assisted method for preparing polyimide foam material

    CN111690136A

  • Biomass-based reinforced polyvinyl alcohol composite material and preparation method thereof

    CN115368694A

  • Long-acting antibacterial polyvinyl acetal sponge and preparation method thereof

    CN116574300A

  • Preparation method and application of antibacterial and fresh-keeping composite sponge

    CN117304559A

  • Polyurethane elastomers, bio-additive compositions

    US20220073674A1